RETURNEE ENTREPRENEURSHIP IN ROMANIA – DETERMINANTS AND PERSPECTIVES - Radu Florin OGARCA; Sorinel DOMNIŞORU; Liviu CRĂCIUN; Laurenţiu MIHAI (Management & Marketing)
The present paper aims to identify and analyze the factors (both favorable and inhibitory) which determine entrepreneurship in the context of the returnee migration and the economic and social impact of entrepreneurship in a specific Romanian context. In order to fulfill these goals, we have collected a set of data through an online survey, which was answered by 92 migrants, which after a period of time spent abroad (for work or studies), returned to Romania and opened their own business. The results of the study are showing that the returnees perceive the Romanian business environment as having many barriers for entrepreneurs. Because of this, many of our respondents are showing a clear intention to leave the country again.